Discipline with Jimmy Hymes - National Association for the Education of Young Children (National Association for the Education of Young Children, 1985)
Entrevista de Carolyn S. Dorrell, a Jimmy Hymes sobre el tema de la disciplina en los niños a nivel de enseñanza preescolar.